Subclonal analysis in a lobular breast cancer with classical and solid growth pattern mimicking a solid‐papillary carcinoma. (19th July 2017) - Christgen, Matthias; Bartels, Stephan; van Luttikhuizen, Jana Lisa; Schieck, Maximilian; Pertschy, Stefanie; Kundu, Sudip; Lehmann, Ulrich; Sander, Bjoern; Pelz, Enrico; Länger, Florian; Schlegelberger, Brigitte; Steinemann, Doris; et al.
Abstract: Recently, a new variant of invasive lobular breast cancer (ILBC) with solid‐papillary‐like growth pattern has been described. We present a case of ILBC with solid‐papillary‐like growth pattern in the main tumour mass and classical invasive lobular growth pattern in adjacent satellite foci. The two tumour components were subjected to comprehensive molecular analyses. Both components were ER/PR‐positive, HER2‐negative, and showed a complete loss of E‐cadherin and beta‐catenin protein expression, as determined by immunohistochemistry. Gene expression profiling classified the main tumour and a satellite focus as luminal‐B and luminal‐A subtypes, respectively. Whole‐genome copy number profiles were highly similar in both tumour components. Shared copy number alterations (CNAs) included gains of chromosome 1q21.1–q43 and losses of chromosome 16q11.2–q24.3, the locus of the CDH1 /E‐cadherin tumour suppressor gene. CNAs detected only in the main tumour included a gain of chromosome 20q12–q13.33 and a loss of chromosome 1p36.33–p34.3, which has recently been associated with the solid variant of ILBC. Next generation sequencing revealed an identical, truncating CDH1 mutation (p.G169fs*5) in both tumour components confirming a common clonal ancestry. In conclusion, we confirm the recently described variant of ILBC with solid‐papillary‐like growth pattern and provide evidence that it evolves from classical ILBC by subclonal evolution.